Molecular epidemiological investigations of human parvovirus B19 among blood donors in Lanzhou - WU Kangle; YANG Shulong; FENG Weiping; WANG Weirong; PAN Deng (Zhongguo shuxue zazhi)
[Objective] To investigate the molecular prevalence and genotype of human parvovirus B19(B19) among blood donors in Lanzhou, and provide data support for monitoring the positive rate of B19 DNA in local blood donors. [Methods] A total of 7 644 blood donor samples collected from January to September 2022 were randomly screened using real-time fluorescent PCR, resulting in 23 samples testing positive for B19 DNA. The characteristics of the B19 DNA reactive donors including gender, age, blood donation recruitment and promotion mode, and donation frequency were analyzed using SPSS 22.0. Additionally, the VP1 gene fragment of B19 DNA reactive samples was sequenced and an evolutionary tree was constructed by the N-J method. [Results] The results showed that the positive rate of B19 DNA in Lanzhou was 0.30%, and the positive population mainly consisted of female individuals aged 18-30 years old who were first-time blood donors; furthermore, genotype 1a was identified as predominant. [Conclusion] The positive rate of B19 DNA is low among blood donors in Lanzhou, with genotype 1a being predominant. It is recommended to periodically monitor the B19 prevalence in blood donors and enhance prevention and control measures, thus improving blood quality and safety.